Penyuluhan Mengenai International Phonetic Alphabet Sebagai Sarana Pemahaman dan Peningkatan Keterampilan dalam Pengucapan Bahasa Inggris yang Akurat di Universitas Sumatera Selatan Palembang - Moehamad Ridhwan; Tiur Simanjuntak; Evi Agustinasari; Risnawati Risnawati; Sunani Sunani (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
This presentation aimed to disseminate knowledge about the International Phonetic Alphabet (IPA) to students of Sumatera Selatan University of Palembang. It is widely recognized that English pronunciation poses challenges due to several reasons. Firstly, many English words are not pronounced as they are spelled. Secondly, diphthongs often lack consistency from the way they are formed, in which combined vowels are producing sounds different from the original in the syllable. Thirdly, some letters are completely silent in certain contexts. Given these difficulties faced by English learners, the presenters sought to highlight the IPA as a practical solution to improve pronunciation accuracy. The feedback gathered after the session indicated that the presentation was highly informative and beneficial, as reflected in the students' responses documented in this report.